"Dearest Susie Pye": New Meredith Letters to Peacock's Natural Daughter. - Joukovsky, Nicholas A. (Studies in Philology)
This article provides full details of a recently discovered cache of letters from George Meredith and his first wife Mary Ellen to Susan Mary Abbott (1830-1921), who in 1858 married William Mayne Neill (1824-1913). The first section focuses on the biographical background of the letters, identifying the recipient as a previously unknown natural daughter of Thomas Love Peacock, and thus a half-sister of Mary Ellen Meredith. The second section provides annotated texts of the letters, which were written in 1854-55, while the Merediths were still living together, and in 1861, more than three years after their separation and just a few months before Mary Ellen's death. Despite Meredith's habitual reserve, these new letters are among the most revealing personal documents to have survived his efforts to suppress all written records of his family background and first marriage. They also throw new light on Meredith's literary work, especially the composition, revision, and publication of his first novel, The Shaving of Shagpat.